La traducción de los aspectos interculturales en el aula de ELE con alumnos polacos de nivel inicial - Del Valle Cacela, Verónica (Studia Romanica Posnaniensia, 2021)
Translation encompasses a complex activity in which we must transfer ideas from a source language to a target language, so that knowledge of the environment surrounding the working languages becomes a necessary competence to carry out the translation activity. Within this knowledge, we must necessarily include the cultural aspects of a language, either from an intercultural or an intracultural perspective. For the purpose of this article, we will focus on how intercultural elements can be developed in the classroom of Spanish as a foreign language. In order to accomplish our aim, we will expose based on empirical analysis the introduction of sociocultural items in university studies with beginners learners (A1-A2) and the result obtained, knowing that the primary objective of this curriculum is to prepare students to be translators or interpreters.